The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/bjsw/bcu107
|View full text |Cite
|
Sign up to set email alerts
|

Educational Determinants of Readiness to Practise with LGBTQ Clients: Social Work Students Speak Out

Abstract: As health and mental health providers are increasingly called to attend to lesbian, gay, bisexual, transgender and queer (LGBTQ) issues, it is critical for social work education to ensure the competency of students to deliver services to these populations. This North American online study investigated the self-assessed readiness of LGBTQ undergraduate and master's-level social work students (n ¼ 1,018) to practise with LGBT clients, as well as their assessment of their non-LGBTQ peers. Participants were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…Educators, practitioners, and researchers alike would benefit from a broader understanding of specific life span and age cohort differences that exist among the LGBT community (Smith et al, 2010). For this trend to continue in a positive manner, however, it is necessary that professionals prepare themselves to work with LGBT older adults such as any other diverse client population as well as to acknowledge the ongoing need for personal and professional growth (Bogo, 2010;Logie et al, 2007;Craig et al, 2014). Only through continued learning and exploration of personal attitudes and beliefs about LGBT and aging issues can this community be effectively, comprehensively, and competently served.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Educators, practitioners, and researchers alike would benefit from a broader understanding of specific life span and age cohort differences that exist among the LGBT community (Smith et al, 2010). For this trend to continue in a positive manner, however, it is necessary that professionals prepare themselves to work with LGBT older adults such as any other diverse client population as well as to acknowledge the ongoing need for personal and professional growth (Bogo, 2010;Logie et al, 2007;Craig et al, 2014). Only through continued learning and exploration of personal attitudes and beliefs about LGBT and aging issues can this community be effectively, comprehensively, and competently served.…”
Section: Resultsmentioning
confidence: 99%
“…In order to effectively expand cohort-specific knowledge and clarify perceptions of LGBT legal, psychosocial, well aging, and health care issues, educators and practitioners alike must ensure expansion and infusion of such topics within the classroom (Logie et al, 2007;Gezinski, 2009;Craig et al, 2014), agency settings, field placements (Messinger, 2011) and counseling offices alike while measuring competency whenever possible. This may be accomplished though broader and ongoing discussions related to policy, advocacy, social justice, and civil rights in order to effectively advocate and increase knowledge of LGBT aging (McFarland & Sanders, 2003), lifespan, and psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LGBTQ (lesbian, gay, bisexual, transgender and queer) social work students (Craig et al, 2016) found low levels of self-assessed readiness to practise with specific subpopulations, particularly trans populations. In addition, the findings of a recent survey undertaken on behalf of Stonewall in the UK (Somerville, 2015), suggest that more than one in ten workers in health and social care settings (including social workers) do not feel confident in their ability to understand or meet the needs of LGB people, and that a quarter of them are not confident in their ability to respond to the specific care needs of trans people.…”
Section: Contextmentioning
confidence: 99%